SARS-CoV-2 D614G spike mutation increases entry efficiency with enhanced ACE2-binding affinity - Seiya Ozono (Nature Portfolio, 2021)
SARS-CoV-2 D614G spike protein mutation is one of the predominant circulating vital mutants. Here, Ozono et al. demonstrate that D614G mutation increases in vitro cell entry by acquiring higher affinity to ACE2.